Jungtinė biblioteka – dar vienas bibliotekų bendradarbiavimo modelis, naujas bibliotekų tipas ar būsima bibliotekų veiklos forma - Pupelienė, Janina; Baliutavičiūtė, Simona (Information & Media, 2010)
Nė viena šiandienė biblioteka individualiai negali suteikti prieigos prie visų vartotojams reikalingų informacijos šaltinių. Prieigos problema nuolat aštrėja ir bibliotekoms tenka spręsti informacijos aprūpinimo bei paklausos suderinimo problemą. Vienas iš galimų sprendimo būdų – glaudesnis bibliotekų bendradarbiavimas, tenkinant vartotojų poreikius. Jau įprastomis bibliotekų bendradarbiavimo formomis tapo įvairūs bibliotekų tinklai, susivienijimai, konsorciumai, asociacijos. Viena iš glaudžiausio bibliotekų bendradarbiavimo formų – jungtinės bibliotekos. Straipsnyje keliama jungtinių bibliotekų kaip naujo reiškinio bibliotekininkystėje problema bei pristatomi vieno iš autorių atlikto jungtinių bibliotekų egzistavimo galimybių Lietuvoje tyrimo rezultatai. Straipsnyje daroma išvada, jog jungtinės bibliotekos – tai perspektyvi bibliotekų veiklos forma.Pagrindiniai žodžiai: mokslinė biblioteka, bibliotekų bendradarbiavimas, jungtinės bibliotekos, viešoji biblioteka, bibliotekų tapatybė.Joint Library – a New Model of Library Co-operation, a New Type of Library or a New Form of Future Libraries?Janina Pupelienė, Simona BaliutavičiūtėSummaryToday, no one individual library can provide access to all information resources needed to their users. The problem of access is growing, and libraries have to accommodate information provision and demand. A possible solution of this problem is a close co- operation of libraries in order to satisfy users’ needs. Various networks, unions, consortiums of libraries are the most common forms of such co-operation. The most radical form of today‘s library co-operation is establishment of joint-use libraries. Library co-operation and particular joint-use libraries are shown as very useful for individual libraries in the article. Authors of the article give attention to various sides of joint-use library practice. They present the latest publications (Hansson, 2010) where the library identity problem while joining different types of libraries have been described.The article presents joint use libraries as a new phenomenon in library science, together with the analysis of the possibilities of such libraries in Lithuania. Considering the existence some joint-use libraries (in all cases public and school libraries are merged) in Lithuania and not very enthusiastic comments on them by some Lithuanian library professionals, authors of the article intend to present this form of joint library activities more widely to stimulate Lithuanian library managers’ interest to this innovative form.Authors believe that the current situation in Lithuania is favourable for adopting good experience of world libraries and organising joint-use libraries in the country.As a kind of a pilot research, library staff and users of two university and county libraries of Lithuanian cities – Klaipėda and Šiauliai – have been questioned in order to discover their opinion on this form of library. According to the results, library users are more enthusiastic about joint-use libraries in their cities than library staff.Both groups of respondents represented quite a similar understanding of the main benefits of joint libraries. As the most positive benefits, comfortable access to all kinds of needed information has been highlighted by 38% of questioned users and by 33% of library staff. Facilities and complexity of transformed library activities have been stressed as the main problematic areas of joint libraries for both librarians and users. A half (54%) of librarians stressed the need of additional skills in case of organising a joint library. The ability to adapt the different needs of users and provision of service for them has been mentioned as the main requirement for these new skills.The study has revealed a lack of information on joint libraries among the library staff and users of the analysed Lithuanian cities. Despite this lack, results of the research concerning the general opinion on joint-use libraries is close to the analysed publications in the world‘s media. The main conclusion of the article: Lithuanian library managers have to value joint-use libraries as an innovative and possible form for the future development of libraries in Lithuania.